Hypervolemia does not cause degradation of the endothelial glycocalyx layer during open hysterectomy performed under sevoflurane or propofol anesthesia. Issue 4 (6th December 2019) - Nemme, Janis; Krizhanovskii, Camilla; Ntika, Stelia; Sabelnikovs, Olegs; Vanags, Indulis; Hahn, Robert G.
Abstract : Background: Fluid‐induced hypervolemia may stimulate the release of natriuretic peptides and cause degradation (shedding) of the endothelial glycocalyx layer. Sevoflurane is believed to protect the glycocalyx, but the importance of using sevoflurane to prevent shedding during routine surgery is unclear. Methods: The plasma concentrations of brain natriuretic peptide and two biomarkers of glycocalyx shedding, syndecan‐1, and heparan sulfate, were measured in 26 patients randomized to receive general anesthesia with sevoflurane or propofol during open abdominal hysterectomy. The fluid therapy consisted of 25 mL/kg (approximately 2 L) of Ringer´s lactate over 30 minutes. Blood hemoglobin and plasma albumin were used to indicate plasma volume expansion and capillary leakage. Results: The plasma concentrations of brain natriuretic peptide and shedding products showed low levels throughout the surgery (median brain natriuretic peptide, 21 ng/L; syndecan‐1, 12.9 ng/mL; and heparan sulfate, 6.5 µg/mL), but the heparan sulfate concentration increased 2 hours post‐operatively (to 17.3 µg/mL, P < .005). No differences were noted between the propofol and sevoflurane groups in any of the measured parameters. Albumin was apparently recruited to the bloodstream during the first 20 minutes, when the intravascular retention of infused fluid was almost 100%. The urine flow was <1 mL/min, despite the vigorous volume loading. Conclusions: No relevant elevations of brain natriuretic peptide or degradation products of the glycocalyx layer were observed when hypervolemia was induced during open abdominal hysterectomy performed with sevoflurane or propofol anesthesia. Plasma volume expansion from Ringer´s lactate was pronounced.